Strategy To Enhance Organizational Capability Of PT Graha Sarana Duta In Preparing Corporate Property Company's Digital Transformation - Advitor Juto Kusmono; Dodie Tricahyono (Cita konsultindo, 2026)
Digital transformation is a strategic necessity that cannot be avoided in the era of technological disruption, including in the property sector. PT Graha Sarana Duta (GSD), a subsidiary of PT Telkom Indonesia engaged in property management, faces challenges such as uneven digitalization across directorates, limited system integration, varying levels of human resource readiness, and suboptimal infrastructure. This study aims to assess GSD’s level of digital transformation readiness using the Digital Maturity Model (DMM), identify key obstacles encountered, and formulate managerial strategies that align with the company’s business characteristics and organizational structure. This research employed a qualitative method through in-depth interviews, field observations, and document studies, involving 15 key informants from four strategic directorates: Operation, Business, Finance and Risk Management, and Planning. All informants have direct responsibilities in operations, finance, marketing, and planning processes, providing a comprehensive perspective on digital readiness across all areas. The findings indicate that GSD’s digital readiness is at an intermediate level, with several business processes already digitized, yet system integration and human resource capability enhancement remain necessary. Major challenges include limited infrastructure, resistance to the digitalization roadmap, and a lack of continuous training. Recommended strategies include strengthening digital leadership, accelerating system integration, improving competencies through structured training, and fostering a data-driven, collaborative work culture.